Hydrogen therapy promotes macrophage polarization to the M2 subtype in radiation lung injury by inhibiting the NF-κB signalling pathway - Xue Gao; Shiying Niu; Lulu Li; Xiaoyue Zhang; Xuetao Cao; Xinhui Zhang; Wentao Pan; Meili Sun; Guoli Zhao; Xuezhen Zheng; Guohua Song; Yueying Zhang (Heliyon, 2024)
Background: Radiotherapy has become a standard treatment for chest tumors, but a common complication of radiotherapy is radiation lung injury. Currently, there is still a lack of effective treatment for radiation lung injury. Methods: A mouse model of radioactive lung injury (RILI) was constructed and then treated with different cycles of hydrogen inhalation. Lung function tests were performed to detect changes in lung function.HE staining was used to detect pathological changes in lung tissue. Immunofluorescence staining was used to detect the polarization of macrophages in lung tissue. Immunohistochemistry was used to detect changes in cytokine expression in lung tissues. Western Blot was used to detect the expression of proteins related to the NF-κB signalling pathway. Results: Lung function test results showed that lung function decreased in the model group and improved in the treatment group.HE staining showed that inflammatory response was evident in the model group and decreased in the treatment group. Immunohistochemistry results showed that the expression of pro-inflammatory factors was significantly higher in the model group, and the expression of pro-inflammatory factors was significantly higher in the treatment group. The expression of pro-inflammatory factors in the treatment group was significantly lower than that in the model group, and the expression of anti-inflammatory factors in the treatment group was higher than that in the model group. Immunofluorescence showed that the expression of M1 subtype macrophages was up-regulated in the model group and down-regulated in the treatment group. The expression of M2 subtype macrophages was up-regulated in the treatment group relative to the model group. Western Blot showed that P–NF-κB p65/NF-κB p65 was significantly increased in the model group, and P–NF-κB p65/NF-κB p65 was decreased in the treatment group. Conclusion: Hydrogen therapy promotes macrophage polarization from M1 to M2 subtypes by inhibiting the NF-κB signalling pathway, thereby attenuating the inflammatory response to radiation lung injury.